Characterizazion of time resolved photodetector systems for Positron Emission Tomography - Powolny, François (My University, 2009)
The main topic of this work is the study of detector systems composed of a scintillator, a photodetector and readout electronics, for Positron Emission Tomography (PET). In particular, the timing properties of such detector systems are studied. The first idea is to take advantage of the good timing properties of the NINO chip, which is a fast preamplifier-discriminator developed for the ALICE Time of flight detector at CERN. This chip uses a time over threshold technique that is to be applied for the first time in medical imaging applications. A unique feature of this technique is that it delivers both timing and energy information with a single digital pulse, the time stamp with the rising edge and the energy from the pulse width. This entails substantial simplification of the entire readout architecture of a tomograph. The scintillator chosen in the detector system is LSO. Crystals of 2x2x10mm3 were used. For the photodetector, APDs were first used, and were then replaced by SiPMs to make use of their higher gain. These different elements that constitute the whole detector system are presented, and their functioning is explained. Within the European FP6 BioCare project, a test setup comprising 2 identical detector systems in coincidence was developed. Each one is composed of a LSO scintillator, an APD, a preamplifier and the NINO readout electronics. The energy resolution was measured to 16% for 511keV y-rays. This is comparable to the resolution obtainable with PMT based systems. The same APD based system was also studied with 122keV X-rays, to assess its potential for combined PET-CT imaging. The energy resolution in this case was measured to 70% as compared to 50% with PMTs. This is explained by a lack of sensitivity of the readout electronics to low charges. The time resolution for 2 such detectors in coincidence was demonstrated to be of 1.6ns FWHM. This is 3 times worse than what one could obtain with PMT based systems under the same conditions. The contributions of the different elements of the detector system to the time precision were identified. The relative contributions of the electronics, the APD and the LSO were found to be 20%, 30% and 50%, respectively. However, the fact that the LSO crystal dominates the time resolution is partly attributed to the readout mechanism of the APD. The relatively low gain of the APD prevents the readout electronics from detecting fewer than 20 photoelectrons coming from the LSO whereas the PMT is sensitive to a single photon. Therefore, a new photodetector was chosen and characterized: the Silicon PhotoMultiplier (SiPM). This photodetector finds increasing interest in the scientific community, offering better characteristics than APD in terms of gain and of single photon sensitivity. They could also be used for TOF applications in PET. The SiPM used were supplied by ST microelectronics and tested at CERN in the context of a scientific collaboration. SiPM from Hamamatsu were also tested for comparison. The study of a 1x1mm2 SiPM has demonstrated that the time resolution of the SiPM coupled to the NINO chip is of 180ps rms from the detection of single 405nm laser photon. This means that this combination of SiPM+NINO can also be used as a detector system for the detection of single photons such as in Cerenkov light detection or in fluorescence spectroscopy, where good time precision is required. In the case of PET, the response of the SiPM to LSO photons following the interaction of a 511keV y-ray was modeled. Since in this case the output current from the SiPM is too high to be directly read out by the NINO circuit, an interface consisting of a differentiating circuit was developed. Furthermore, the typical size of LSO crystals (2x2mm2) together with the high number of SPAD cells required to detect the photons emitted by the LSO implies that larger size SiPM (3x3mm2) have to be used. The work done during the thesis has shown a crucial influence of the SiPM terminal capacitance, which may be as high as 320pF for the Hamamatsu SiPM of 3x3mm2. In contrast with SiPMs of smaller size, this capacitance in parallel with a load resistance (e.g. scope or NINO) is large enough to significantly increase the rise time of the SPAD signals to the extent that the timing performance of the ensemble is severely degraded. An improved electronics interface is currently being studied to overcome this limitation. Another novel photodetector has also been studied in the context of this thesis: the microchannel plate (MCP) that is made of hydrogenated amorphous silicon (a-Si:H). The first samples were developed at the Institute of MicroTechnology (IMT) of Neuchatel and tested at CERN in a scientific collaboration. The advantage of this detector is the possibility to deposit on top of ASIC in a direct and vertical integration. Our preliminary investigation indicate that a current increase takes place along the borders of the MCP pores, possibly indicating the generation of a cascade of secondary electrons.
Thèse de doctorat : Université de Neuchâtel, 2009 ; Th. 2107
Keywords: photodétecteur; scintillateur; système de détection résolu en temps; "time over threshold" méthode; Tomographie par Emission de Positron (TEP); Silicium amorphe hydrogéné; photodetector; Scintillator; time over threshold method, time resolved detection system; Positron Emission Tomography (PET), Hydrogenated amorphous silicon (a-Si:H).